Aerodynamic and performance characteristics of a passive leading edge Kruger flap at low Reynolds numbers - Moraris, Vassilis Michael; Lawson, Nicholas J.; Garry, Kevin P. (Royal Aeronautical Society, 2012)
An experimental and numerical study was performed on a Clark Y aerofoil with a 10% chord leading edge Kruger flap to examine its aerodynamic performance at Reynolds numbers of 0.6 × 106, 1 × 106, and 1.6 × 106, to help to identify the forces and moments acting on a basic configuration. A detailed comparison of the numerical and experimental data is presented in this paper. The leading edge flap was effective at high angles of attack with an increase in CL of up to 18% over a conventional no flap configuration and delayed separation by up to 3°. The moments around the Kruger flap rotation point were calculated from the numerical analysis as an initial stage in the design of a UAV passive flap system and they are also presented in the pa